The Determinants of public debt in Pakistan - IMRAN, Muhammad (KDI School, 2016)
Public debt and its sustainability have emerged as one of the core areas of concern in previous three decades. Pakistan, being a developing country has always remained confronted with the issue of debt overhang owing to its macroeconomic and political factors. This study, by using Pakistan as a case study and empirical method of ARDL cointegration, tries to enquire about the determinants of public debt by using data for the period 1970 to 2012. The study finds that inflation and economic growth have a significant restraining effect on public debt while openness has no significant impact on public debt. Political regime wise, the instant study throws out two contrasting details whereby inflation is the major determinant of public debt in democratic regimes while growth appears as a significant factor in autocratic periods. According to the findings, it may be inferred that inflation lowers down the higher impact of interest rates for the debt. In essence however, it implies that resort to inflationary methods without accompanying growth may arrest the debt surge but leaves the economy prone to other repercussions. The impact of economic growth as a determining factor suggests that stimulus in economic growth creates the fiscal space and improves the debt dynamics thus limiting the need of public debt as a source of finance.
Thesis(Master) --KDI School:Master of Public Policy,2016